PERFORMANCE OF BALI HEIFERS AND CALVES PRIOR TO WEANING IN A FEEDLOT SYSTEM - O K A, I. G. L . (Majalah Ilmiah Peternakan; Vol 8 No 2 (2005), 2012)
S U M M A R Y A study on performance of Bali heifers and their first calves kept in a feedlot system was carried out using 20 heifers fed two feeding regimes namely elephant grass only ( group A ) and a mixture of 40 % elephant grass and 60 % concentrate containing 20.7 % CP and 77.3 % TDN ( group B ). Liveweight up to calving, production and quality of milk, calfbirth, and daily gain prior to weaning in this cattle breed were significantly affected (P>0.05) by concentrate supplementation. However, service per conception and gestation length was not significantly (P>0.05) different between the two groups of feeding regimes. It seemed that in the short term, improvement in management particularly feeding a higher quality ration was needed to overcome the problem in performance degradation of Bali cattle which has become some concerned recently.